Fear, Populism, and the Geopolitical Landscape: The "Sleeper Effect" of Neurotic Personality Traits on Regional Voting Behavior in the 2016 Brexit and Trump Elections. Issue 3 (April 2018) - Obschonka, Martin; Stuetzer, Michael; Rentfrow, Peter J.; Lee, Neil; Potter, Jeff; Gosling, Samuel D.
Two recent electoral results—Donald Trump's election as U.S. president and the UK's Brexit vote—have reignited debate on the psychological factors underlying voting behavior. Both campaigns promoted themes of fear, lost pride, and loss aversion, which are relevant to the personality dimension of neuroticism, a construct previously not associated with voting behavior. To that end, we investigate whether regional prevalence of neurotic personality traits (neuroticism, anxiety, and depression) predicted voting behavior in the United States ( N = 3, 167, 041) and the United Kingdom ( N = 417, 217), comparing these effects with previous models, which have emphasized the roles of openness and conscientiousness. Neurotic traits positively predicted share of Brexit and Trump votes, and Trump gains from Romney. Many of these effects persisted in additional robustness tests controlling for regional industrial heritage, political attitude, and socioeconomic features, particularly in the United States. The "sleeper effect" of neurotic traits may profoundly impact the geopolitical landscape.